A LiAlSiO4-coated modified cathode material, its preparation method and application

CN121672599BActive Publication Date: 2026-10-23GEM (HUBEI) NEW ENERGY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511921020.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-18
Publication Date
2026-10-23
Estimated Expiration
2045-12-18

AI Technical Summary

Technical Problem

[0005]鉴于背景技术中存在的技术问题,本发明提供了一种LiAlSiO4包覆改性正极材料及其制备方法和应用,旨在解决现有电极材料表面结构不稳定和循环容量快速衰减的技术问题

Benefits of technology

(1)本发明选取具有热膨胀特性的LiAlSiO4快离子导体作为包覆层,能够有效抑制高镍正极循环过程的体积膨胀,并且实现铝掺杂,提高材料的电化学性能。LiAlSiO4作为快离子导体包覆层能够为Li+在正极和电解质界面提供稳定的迁移路径,同时还能有效阻止电解液对正极材料表面的腐蚀,提高倍率性能和循环性能。所得的改性三元正极材料具有较高的电导率,能够避免电解液对正极活性物质的侵蚀。将该改性三元正极材料进一步制备成电池,能够使电池具有较高的放电比容量以及良好的循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121672599B_ABST
    Figure CN121672599B_ABST
Patent Text Reader

Abstract

The application provides a LiAlSiO4-coated modified positive electrode material and a preparation method and application thereof, and the preparation method comprises the following steps: dissolving an aluminum salt in an alkali solution to obtain an aluminum-alkali mixed solution; mixing a nickel-cobalt-manganese metal mixed solution, an alkali solution and ammonia water to perform a co-precipitation reaction, adding the aluminum-alkali mixed solution when the particles grow to a first target particle size, and obtaining nickel-cobalt-manganese hydroxide coated with an aluminum layer on the surface when the particles grow to a second target particle size, sintering to obtain a first modified precursor; mixing with a silicon source alkali solution, uniformly stirring at room temperature, drying to obtain a second modified precursor; mixing with a lithium source, sintering, grinding to obtain the LiAlSiO4-coated modified positive electrode material. The application realizes uniform coating of the LiAlSiO4-coated agent on the surface of a high-nickel ternary positive electrode material and reduces residual alkali on the surface, and the lithium battery prepared from the modified positive electrode material has a high discharge specific capacity and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery cathode material technology, specifically to a LiAlSiO4 coated modified cathode material, its preparation method, and its application. Background Technology

[0002] Lithium-ion batteries boast longer charge-discharge cycles, higher voltage platforms, and higher energy densities. These advantages have made them a primary energy storage device for commercial rechargeable battery applications and cutting-edge scientific research. Current lithium-ion battery technology needs upgrading to achieve even higher energy densities (>350 Wh / kg). High-nickel ternary cathode materials (LiNi) are crucial. x Co y Mn z The high theoretical specific capacity (>270 mA·g) of O2 (x+y+z=1) is highly suitable for high-energy-density lithium-ion battery systems and is key to technological upgrades. High-nickel ternary materials are typically prepared using co-precipitation and solid-state sintering methods. In this process, nickel-cobalt-manganese ternary hydroxide [Ni x Co y Mn z [(OH)2] is an important intermediate obtained by coprecipitation, but preparing a single-phase ternary precursor is challenging because the solubility products of Ni, Co, and Mn hydroxides are different; the solubility product of Mn(OH)2 at room temperature is on the order of 10. -13 Compared to Ni(OH)2 and Co(OH)2, 10 -15 The nickel content is approximately two orders of magnitude higher. If unsuitable synthesis conditions are used, hydroxide phase separation can easily occur, making it impossible to obtain a pure-phase layered ternary precursor. Most importantly, the morphology, particle size, and crystal structure of the high-nickel ternary precursor material have a decisive influence on the physicochemical properties and electrochemical performance of the sintered high-nickel ternary cathode material. Therefore, exploring preparation processes and developing ternary precursors with specific properties is fundamental to the production of high-performance ternary cathode materials.

[0003] Because high-nickel ternary cathode materials have a high Ni content, they tend to form more Ni during battery charging compared to low-nickel and medium-nickel materials. 4+ These highly oxidizing Ni 4+ It is unstable and readily reacts with the electrolyte to be reduced to Ni. 2 +Meanwhile, high-nickel ternary cathode materials often experience excessive lithium delithiation during charging, leading to the formation of an inert metal oxide layer (NiO, or rock salt phase) on the material surface. This hinders lithium-ion transport between the positive and negative electrodes, resulting in increased battery impedance. The rock salt phase often forms during the first few charge-discharge cycles and continues to negatively impact battery performance and capacity decay during subsequent cycles.

[0004] Currently, surface coating can address the problems of unstable electrode material surface structure and rapid capacity decay caused by side reactions occurring when the electrode material comes into contact with the electrolyte. Existing coating materials commonly use oxides, carbon coatings, and fast ion conductor coatings. While these materials can optimize material performance to some extent, they cannot suppress the bulk expansion of high-nickel particles, and they cannot reduce the residual alkali in the cathode material. Therefore, there is an urgent need to develop a new surface coating modification method to improve material performance. Summary of the Invention

[0005] In view of the technical problems existing in the background art, the present invention provides a LiAlSiO4 coated modified cathode material, its preparation method and application, aiming to solve the technical problems of unstable surface structure and rapid capacity decay of existing electrode materials.

[0006] In a first aspect, the present invention provides a method for preparing a LiAlSiO4 coated modified cathode material, comprising the following steps: S1. Dissolve nickel salt, cobalt salt, and manganese salt in water to obtain a mixed metal solution; S2. Dissolve aluminum salt in alkaline solution to obtain aluminum-alkali mixed solution; S3. The metal mixed solution, alkaline solution and ammonia water are slowly added to the bottom liquid of the reactor to carry out a co-precipitation reaction. When the particles grow to the first target particle size, the aluminum-alkali mixed solution is added to the reactor simultaneously. When the particles grow to the second target particle size, the reaction ends. After aging, washing, dehydration and drying, nickel-cobalt-manganese hydroxide with an aluminum coating is obtained. The first sintering is carried out to obtain the first modified precursor. S4. Dissolve the silicon source in an alkaline solution to obtain a silicon source solution; mix the first modified precursor with the silicon source solution, stir evenly at room temperature, and dry to obtain the second modified precursor; S5. The second modified precursor is mixed with the lithium source, sintered, and ground to obtain the LiAlSiO4 coated modified cathode material.

[0007] Preferably, in step S1, the nickel salt includes at least one of nickel sulfate, nickel chloride, and nickel nitrate; the cobalt salt includes at least one of cobalt sulfate, cobalt chloride, and cobalt nitrate; and the manganese salt includes at least one of manganese sulfate, manganese chloride, and manganese nitrate.

[0008] Preferably, in step S3, the base solution is obtained by mixing water, alkali solution and ammonia solution, the pH of the base solution is 10~14, and the ammonia concentration of the base solution is 10~15g / L; during the coprecipitation reaction, the pH is controlled at 10~14, the ammonia concentration is 10~15g / L, the rotation speed is 300~1100rpm, and the reaction temperature is 30~65℃.

[0009] Preferably, in step S3, when the aluminum-alkali mixed solution is simultaneously dripped into the reactor, the molar ratio of Al element in the aluminum-alkali mixed solution to nickel, cobalt and manganese metal elements in the metal mixed solution is a:(100-a), 0.5≤a≤3.

[0010] Preferably, in step S3, the chemical formula of the nickel-cobalt-manganese hydroxide with an aluminum coating layer is Ni x Co y Mn z Al (1-x-y-z) (OH)2, where x≥0.85, 0.01<y<0.1, 0.01<z<0.1.

[0011] Preferably, in step S3, the first target particle size is 9.0~10.0μm, the second target particle size is 10.0~11.0μm, the first sintering temperature is 400~500℃, and the first sintering time is 8~12h.

[0012] Preferably, in step S4, the silicon source includes anhydrous sodium metasilicate and / or sodium metasilicate hydrate; the concentration of the silicon source solution is 0.02~0.05mol / L, and the pH of the silicon source solution is 10~11; the solid-liquid ratio of the first modified precursor to the silicon source solution is 1g:(15~20)mL.

[0013] Preferably, in step S5, when the second modified precursor is mixed with the lithium source, the molar ratio Li:Me is controlled to be (1.03-1.05):1, where Me represents Ni, Co, Mn and Al; the lithium source includes lithium hydroxide and / or lithium carbonate; the second sintering temperature is 800~900℃, the second sintering time is 15~20h, and the sintering atmosphere of the second sintering is pure oxygen.

[0014] Secondly, the present invention provides a LiAlSiO4 coated modified cathode material, which is prepared by the preparation method described in the first aspect.

[0015] Thirdly, the present invention provides a lithium battery whose raw materials include the LiAlSiO4 coated and modified cathode material described in the second aspect.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention selects LiAlSiO4, a fast ion conductor with thermal expansion characteristics, as the coating layer. This effectively suppresses the volume expansion during the cycling process of the high-nickel cathode and enables aluminum doping, thereby improving the electrochemical performance of the material. LiAlSiO4, as a fast ion conductor coating layer, can provide a suitable coating for Li... + This modified ternary cathode material provides a stable migration path at the cathode-electrolyte interface and effectively prevents electrolyte corrosion of the cathode material surface, thus improving rate performance and cycle performance. The resulting modified ternary cathode material exhibits high conductivity, preventing electrolyte erosion of the cathode active material. Further fabrication of this modified ternary cathode material into a battery results in a battery with high discharge specific capacity and excellent cycle performance.

[0017] (2) The preparation method of LiAlSiO4-coated modified cathode material provided by the present invention adopts the preparation path of "high-nickel ternary precursor - aluminum doping - silicide - lithiation", which can achieve uniform coating of the coating agent on the surface of the ternary cathode material and reduce the residual alkali on the cathode material surface. Adding an aluminum source and pre-sintering in the later stage of the precursor preparation process can achieve uniform doping of aluminum source and aluminum enrichment on the surface. When the pre-sintered precursor is coated with silicon in a mixed solution of Na2SiO3 and sodium hydroxide, the dissolution of aluminum under alkaline conditions can be suppressed. The modified precursor is sintered with lithium to obtain LiAlSiO4-coated modified high-nickel cathode material. When the LiAlSiO4 coating layer is formed, it will combine with the residual alkali on the material surface, which can reduce the residual alkali. The synthesis process provided by the present invention is simple and has good commercialization potential and economic benefits. Attached Figure Description

[0018] Figure 1 This is a SEM image of the LNCM@LiAlSiO4 modified cathode material prepared in Example 1 of this invention; Figure 2 This is a SEM image of the LNCM cathode material prepared in Comparative Example 1 of the present invention. Detailed Implementation

[0019] The embodiments of the technical solution of the present invention will now be described in detail with reference to the accompanying drawings. These embodiments are merely illustrative of the technical solution of the present invention and are therefore intended to limit the scope of protection of the present invention.

[0020] To address the technical problems of unstable surface structure and rapid capacity decay in existing electrode materials, this invention provides a LiAlSiO4-coated modified cathode material, its preparation method, and its application. The preparation path of "high-nickel ternary precursor - aluminum doping - silicide - lithiation" achieves uniform coating of LiAlSiO4 coating agent on the surface of high-nickel ternary cathode material, while also reducing residual alkali on the cathode material surface.

[0021] In a first aspect, embodiments of the present invention provide a method for preparing a LiAlSiO4-coated modified cathode material, comprising the following steps: S1. Dissolve nickel salt, cobalt salt, and manganese salt in water to obtain a mixed metal solution; S2. Dissolve aluminum salt in alkaline solution to obtain aluminum-alkali mixed solution; S3. The metal mixed solution, alkaline solution and ammonia water are slowly added to the bottom liquid of the reactor to carry out a co-precipitation reaction. When the particles grow to the first target particle size, the aluminum-alkali mixed solution is added to the reactor simultaneously. When the particles grow to the second target particle size, the reaction ends. After aging, washing, dehydration and drying, nickel-cobalt-manganese hydroxide with an aluminum coating is obtained. The first sintering is carried out to obtain the first modified precursor. S4. Dissolve the silicon source in an alkaline solution to obtain a silicon source solution; mix the first modified precursor with the silicon source solution, stir evenly at room temperature, and dry to obtain the second modified precursor; S5. The second modified precursor is mixed with the lithium source, sintered, and ground to obtain the LiAlSiO4 coated modified cathode material.

[0022] In the technical solution of this invention embodiment, a co-precipitation process is used to prepare a high-nickel precursor. An aluminum source is added in the later stage of the high-nickel precursor preparation process before pre-sintering, which can achieve uniform doping of the aluminum source and aluminum enrichment on the surface. When the pre-sintered precursor is coated with silicon in a mixed solution of silicon source and alkaline solution, the dissolution of aluminum under alkaline conditions can be suppressed. The modified precursor after silicon coating is sintered with lithium to obtain LiAlSiO4 coated modified high-nickel cathode material. Under high temperature conditions, when the LiAlSiO4 coating layer is formed, it will combine with the residual alkali on the material surface, which can reduce the residual alkali. LiAlSiO4 has thermal expansion characteristics, which can alleviate the thermal expansion of high-nickel materials while improving the electrochemical performance of the material.

[0023] Furthermore, in some embodiments, in step S1, the nickel salt includes at least one of nickel sulfate, nickel chloride, and nickel nitrate; the cobalt salt includes at least one of cobalt sulfate, cobalt chloride, and cobalt nitrate; and the manganese salt includes at least one of manganese sulfate, manganese chloride, and manganese nitrate.

[0024] Furthermore, in some embodiments, in step S1, the total concentration of metal ions in the metal mixed solution is 1~5 mol / L.

[0025] Furthermore, in some embodiments, in step S2, the concentration of aluminum salt in the aluminum-alkali mixed solution is 1~5 g / L.

[0026] Furthermore, in some embodiments, in step S3, the base solution is obtained by mixing water, alkaline solution and ammonia solution, the pH of the base solution is 10-14, and the ammonia concentration of the base solution is 10-15 g / L.

[0027] Furthermore, in some embodiments, in step S3, the pH is controlled at 10-14, the ammonia concentration at 10-15 g / L, the rotation speed at 300-1100 rpm, and the reaction temperature at 30-65°C during the coprecipitation reaction.

[0028] Furthermore, in some embodiments, in step S3, when the aluminum-alkali mixed solution is simultaneously dripped into the reactor, the molar ratio of Al element in the aluminum-alkali mixed solution to nickel, cobalt and manganese metal elements in the metal mixed solution is a:(100-a), 0.5≤a≤3.

[0029] Furthermore, in some embodiments, in step S3, the chemical formula of the nickel-cobalt-manganese hydroxide with the aluminum coating layer is Ni x Co y Mn z Al (1-x-y-z) (OH)2, where x≥0.85, 0.01<y<0.1, 0.01<z<0.1.

[0030] Furthermore, in some embodiments, in step S3, the first target particle size is 9.0~10.0 μm, and the second target particle size is 10.0~11.0 μm.

[0031] Furthermore, in some embodiments, in step S3, the temperature of the first sintering is 400~500℃, and the time of the first sintering is 8~12h.

[0032] In the technical solution of this invention embodiment, the main purpose of the first sintering is to perform preliminary heat treatment on the nickel-cobalt-manganese hydroxide with an aluminum coating layer on the surface, promoting the decomposition and preliminary crystal transformation of the hydroxide, and laying a good structural foundation for the subsequent reaction with the silicon source and the final lithiation sintering. Since aluminum hydroxide is amphoteric, sintering can avoid the risk of surface aluminum hydroxide dissolving when subsequently added to the alkaline solution of the silicon source, avoiding the loss of the aluminum layer, thereby ensuring that the subsequently formed LiAlSiO4 coating layer can function uniformly and effectively.

[0033] Furthermore, in some embodiments, in step S4, the silicon source includes anhydrous sodium metasilicate and / or sodium metasilicate hydrate.

[0034] Furthermore, in some embodiments, in step S4, the concentration of the silicon source solution is 0.02~0.05 mol / L, and the pH of the silicon source solution is 10~11.

[0035] Furthermore, in some embodiments, in step S4, the solid-liquid ratio of the first modified precursor to the silicon source solution is 1 g: (15~20) mL.

[0036] Furthermore, in some embodiments, in step S5, when the second modified precursor is mixed with the lithium source, the molar ratio Li:Me is controlled to be (1.03-1.05):1, where Me represents Ni, Co, Mn and Al.

[0037] Furthermore, in some embodiments, in step S5, the lithium source includes lithium hydroxide and / or lithium carbonate.

[0038] Furthermore, in some embodiments, in step S5, the temperature of the second sintering is 800~900℃, the time of the second sintering is 15~20h, and the sintering atmosphere of the second sintering is pure oxygen.

[0039] Secondly, embodiments of the present invention provide a LiAlSiO4 coated modified cathode material, which is prepared by the preparation method described in the first aspect.

[0040] Thirdly, embodiments of the present invention provide a lithium battery whose raw materials include the LiAlSiO4 coated and modified cathode material described in the second aspect.

[0041] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0042] Example 1 A method for preparing LiAlSiO4-coated modified cathode material, the specific steps of which are as follows: (1) Prepare a metal mixed solution with a total concentration of 2.2 mol / L by mixing nickel sulfate, cobalt sulfate and manganese sulfate with pure water, wherein the molar ratio of nickel, cobalt and manganese is 90:5:5; (2) Dissolve aluminum sulfate in an alkaline solution to prepare an aluminum-alkali mixed solution with a concentration of 2 g / L; (3) Use pure water, concentrated alkali and concentrated ammonia as the bottom liquid of the reaction vessel, adjust the pH value to 11.60 and the ammonia concentration to 10.5 g / L; (4) The metal mixed solution, concentrated alkali and concentrated ammonia obtained in step (1) are gradually added dropwise into the reaction vessel. The pH value is controlled at 11.50, the ammonia concentration is 10.5g / L, the rotation speed is 600rpm, and the reaction temperature is 60℃. When the particle size grows to 9-10μm, the aluminum-alkali mixed solution prepared in step (2) is added dropwise into the reaction vessel at a molar ratio of NCM:Al=97:3. When the particle size grows to 10.0-11.0μm, the reaction ends. The sample after the reaction is completed is aged, washed, dehydrated and dried, and placed in a muffle furnace and sintered at 450℃ for 10 hours to obtain the aluminum modified precursor. (5) Dissolve an appropriate amount of anhydrous sodium metasilicate (Na2SiO3) in sodium hydroxide solution to maintain the pH of the solution at 10.5 and the concentration of Na2SiO3 at 0.03 mol / L; (6) Add the aluminum-modified precursor prepared in step (4) to the Na2SiO3 solution prepared in step (5) with a solid-liquid ratio of 1g:15mL, stir evenly at room temperature, and then dry at 80℃ to obtain the silicon-modified precursor. (7) The silicon-modified precursor obtained in step (6) and lithium hydroxide are thoroughly mixed, and the molar ratio of Li:Me is controlled to be 1.04:1, where Me represents the total number of moles of Ni, Co, Mn and Al; (8) The mixture obtained in step (7) is placed in an atmosphere furnace and heated to 850°C at a heating rate of 5°C. Then, it is kept at this temperature for 17 hours. The entire sintering process is carried out in a flowing pure oxygen atmosphere. After the predetermined sintering time is completed, the heating is stopped and the mixture is cooled. Finally, the LiAlSiO4 coated modified cathode material is obtained by grinding, which is denoted as LNCM@LiAlSiO4 cathode material.

[0043] Comparative Example 1 A method for preparing LNCM cathode material, the specific steps of which are as follows: (1) Prepare a metal mixed solution with a total concentration of 2.2 mol / L by mixing nickel sulfate, cobalt sulfate and manganese sulfate with pure water, wherein the molar ratio of nickel, cobalt and manganese is 90:5:5; (2) Use pure water, concentrated alkali and concentrated ammonia as the bottom liquid of the reaction vessel, adjust the pH value to 11.60 and the ammonia concentration to 10.5 g / L; (3) The metal mixed solution, concentrated alkali and concentrated ammonia obtained in step (1) are gradually added dropwise into the reaction vessel. The pH value is controlled at 11.50, the ammonia concentration is 10.5 g / L, the rotation speed is 600 rpm, the reaction temperature is 60℃, and the reaction ends when the particle size grows to 10.0-11.0 μm. The sample after the reaction is completed is aged, washed, dehydrated and dried to finally obtain the high nickel precursor sample. (4) Mix an appropriate amount of the high-nickel precursor obtained in step (3) with lithium hydroxide, and control the molar ratio of Li:Me = 1.04:1, where Me represents the total number of moles of Ni, Co and Mn; (5) The mixture obtained in step (4) is placed in an atmosphere furnace and heated to 850°C at a heating rate of 5°C. Then, it is kept at this temperature for 17 hours. The entire sintering process is carried out in a flowing pure oxygen atmosphere. After the predetermined sintering time is completed, the heating is stopped and the mixture is cooled. Then, it is ground to finally obtain a high-nickel cathode material, which is denoted as LNCM cathode material.

[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that the aluminum source and the lithium source are added and mixed together. The specific steps are as follows: (1) Prepare a metal mixed solution with a total concentration of 2.2 mol / L by mixing nickel sulfate, cobalt sulfate and manganese sulfate with pure water, wherein the molar ratio of nickel, cobalt and manganese is 90:5:5; (2) Use pure water, concentrated alkali and concentrated ammonia as the bottom liquid of the reaction vessel, adjust the pH value to 11.60 and the ammonia concentration to 10.5 g / L; (3) The metal mixed solution, concentrated alkali and concentrated ammonia obtained in step (1) are gradually added dropwise into the reaction vessel. The pH value is controlled at 11.50, the ammonia concentration is 10.5 g / L, the rotation speed is 600 rpm, the reaction temperature is 60℃, and when the particle size grows to 10.0-11.0 μm, the sample after the reaction is completed is aged, washed, dehydrated and dried to obtain nickel cobalt manganese hydroxide precursor sample; (4) Dissolve an appropriate amount of anhydrous sodium metasilicate (Na2SiO3) in sodium hydroxide solution to maintain the pH of the solution at 10.5 and the concentration of Na2SiO3 at 0.03 mol / L; (5) The nickel cobalt manganese hydroxide precursor prepared in step (3) is added to the Na2SiO3 solution prepared in step (4) to make the solid-liquid ratio 1:15 (g:mL), stirred evenly at room temperature, and then dried at 80°C to obtain the modified precursor. (6) The modified precursor, alumina and lithium hydroxide obtained in step (5) are thoroughly mixed, and the molar ratio of Li:Me is controlled to be 1.04:1, where Me represents the total number of moles of Ni, Co, Mn and Al, and the molar ratio of Al in the total metals of Ni, Co, Mn and Al is 3%; (7) The mixture obtained in step (6) is placed in an atmosphere furnace and heated to 850°C at a heating rate of 5°C. Then, it is kept at this temperature for 17 hours. The entire sintering process is carried out in a flowing pure oxygen atmosphere. After the predetermined sintering time is completed, the heating is stopped and the mixture is cooled. Finally, the modified cathode material is obtained by grinding.

[0045] Comparative Example 3 Compared with Example 1, this comparative example differs in that only LiAlO2 coating is performed, and the aluminum source and lithium source are added and mixed together. The specific steps are as follows: (1) Prepare a metal mixed solution with a total concentration of 2.2 mol / L by mixing nickel sulfate, cobalt sulfate and manganese sulfate with pure water, wherein the molar ratio of nickel, cobalt and manganese is 90:5:5; (2) Use pure water, concentrated alkali and concentrated ammonia as the bottom liquid of the reaction vessel, adjust the pH value to 11.6 and the ammonia concentration to 10.5 g / L; (3) The metal mixed solution, concentrated alkali and concentrated ammonia obtained in step (1) are gradually added dropwise into the reaction vessel. The pH value is controlled at 11.50, the ammonia concentration is 10.5 g / L, the rotation speed is 600 rpm, the reaction temperature is 60℃, and when the particle size grows to 10.0-11.0 μm, the sample after the reaction is completed is aged, washed, dehydrated and dried to obtain the precursor sample. (4) The precursor, alumina and lithium hydroxide obtained in step (3) are thoroughly mixed, and the molar ratio of Li:Me is controlled to be 1.04:1, where Me represents the total number of moles of Ni, Co, Mn and Al, and the molar ratio of Al in the total metals of Ni, Co, Mn and Al is 3%; (5) The mixture obtained in step (4) is placed in an atmosphere furnace and heated to 850°C at a heating rate of 5°C. Then, it is kept at this temperature for 17 hours. The entire sintering process is carried out in a flowing pure oxygen atmosphere. After the predetermined sintering time is completed, the heating is stopped and the mixture is cooled. Finally, the modified cathode material is obtained by grinding, which is denoted as LNCM@LiAlO2.

[0046] Comparative Example 4 The difference between this comparative example and Example 1 is that silicon coating is performed directly after aluminum coating without sintering. The specific steps are as follows: (1) Prepare a metal mixed solution with a total concentration of 2.2 mol / L by mixing nickel sulfate, cobalt sulfate and manganese sulfate with pure water, wherein the molar ratio of nickel, cobalt and manganese is 90:5:5; (2) Dissolve aluminum sulfate in an alkaline solution to prepare an aluminum-alkali mixed solution with a concentration of 2 g / L; (3) Use pure water, concentrated alkali and concentrated ammonia as the bottom liquid of the reaction vessel, adjust the pH value to 11.6 and the ammonia concentration to 10.5 g / L; (4) The metal mixed solution, concentrated alkali and concentrated ammonia obtained in step (1) are gradually added dropwise into the reaction vessel. The pH value of the reaction is controlled at 11.50, the ammonia concentration is 10.5 g / L, the rotation speed is 600 rpm, the reaction temperature is 60℃, and when the particle size grows to 9.0-10.0 μm, the aluminum-alkali mixed solution prepared in step (2) is added dropwise into the reaction vessel at a molar ratio of NCM:Al=97:3. When the particle size grows to 10.0-11.0 μm, the reaction ends. The sample after the reaction is completed is aged, washed, dehydrated and dried to obtain the aluminum modified precursor sample. (5) Dissolve an appropriate amount of anhydrous sodium metasilicate (Na2SiO3) in sodium hydroxide solution to maintain the pH of the solution at 10.5 and the concentration of Na2SiO3 at 0.03 mol / L; (6) Add the aluminum-modified precursor prepared in step (4) to the Na2SiO3 solution prepared in step (5) with a solid-liquid ratio of 1g:15mL, stir evenly at room temperature, and then dry at 80℃ to obtain the silicon-modified precursor. (7) The silicon-modified precursor obtained in step (6) and lithium hydroxide are thoroughly mixed, and the molar ratio of Li:Me is controlled to be 1.04:1, where Me represents the total number of moles of Ni, Co, Mn and Al; (8) The mixture obtained in step (7) is placed in an atmosphere furnace and heated to 850°C at a heating rate of 5°C. Then, it is kept at this temperature for 17 hours. The entire sintering process is carried out in a flowing pure oxygen atmosphere. After the predetermined sintering time is completed, the heating is stopped and the mixture is cooled. Finally, the modified cathode material is obtained by grinding.

[0047] Performance testing The cathode materials obtained in each embodiment and comparative example were used to prepare coin cells. The preparation method was as follows: LiAlSiO4-coated modified cathode material, polyvinylidene fluoride (PVDF), and conductive carbon black SP were homogenized in a mass ratio of 97.2:1.3:1.5. Then, aluminum foil was laid flat on a coating machine for coating (area density 15~17 mg / cm²). 2 After drying at 80℃ for 2 hours, the material is drilled, weighed, and the electrode sheet is baked to serve as the positive electrode. The negative electrode is made of lithium metal sheet, thus forming a CR2032 button cell.

[0048] The battery was placed in the Blue Battery testing system, and its electrical performance was tested under normal temperature conditions. The test parameters were set as follows: voltage range 2.5V-4.25V, 100 cycles of 0.2C / 0.2C→0.2C / 1C→0.2C / 1C→0.5C / 0.1C. The test results are shown in Table 1 below.

[0049] Table 1

[0050] Test results show that the LNCM@LiAlSiO4 cathode material prepared in Example 1 has a capacity retention rate of up to 92.7% after 100 cycles at 1C, while the LNCM cathode material of Comparative Example 1 without coating modification has a capacity retention rate of only 87.7% after 100 cycles. This indicates that the LiAlSiO4 coating modification of the present invention can significantly improve the cycle stability of high-nickel cathode materials.

[0051] Compared with Comparative Example 2 (where aluminum and lithium sources were added together), the battery performance of Example 1 was better. This is because in Comparative Example 2, aluminum and lithium sources were mixed together, which made it difficult to achieve uniform coating of aluminum on the surface of the material and may also lead to an increase in residual alkali in the cathode material.

[0052] Comparative Example 3 only used LiAlO2 coating, and its capacity retention rate after 100 cycles was 90.6%, which was lower than that of Example 1 and Comparative Example 2. Although LiAlO2 coating can optimize material performance, the use of alumina as aluminum source and physical mixing followed by sintering resulted in relatively poor coating uniformity. At the same time, LiAlO2 coating modification could not alleviate the volume expansion phenomenon of high-nickel materials, and the cathode particles would break during cycling.

[0053] In Comparative Example 4, the battery cycle performance decreased because silicon coating was applied directly without pre-sintering after aluminum modification. This is because after the precursor is coated with aluminum, the surface aluminum exists in the form of aluminum hydroxide. Aluminum hydroxide is an amphoteric substance. When added to a mixed solution of sodium metasilicate and sodium hydroxide, the surface aluminum hydroxide will dissolve, resulting in the absence of the aluminum layer. This reduces the uniformity and integrity of the final coating layer, causing surface abnormalities.

[0054] It should be noted that the present invention is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments that have the same structure and perform the same effects as the technical concept within the scope of the present invention are included within the scope of the present invention. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of the present invention, are also included within the scope of the present invention.

Claims

1. A method for preparing a LiAlSiO4 coated modified cathode material, characterized in that, Includes the following steps: S1. Dissolve nickel salt, cobalt salt, and manganese salt in water to obtain a mixed metal solution; S2. Dissolve aluminum salt in alkaline solution to obtain aluminum-alkali mixed solution; S3. The metal mixed solution, alkaline solution and ammonia water are slowly added to the bottom liquid of the reactor for co-precipitation reaction. When the particles grow to the first target particle size, the aluminum-alkali mixed solution is added to the reactor simultaneously. When the particles grow to the second target particle size, the reaction ends. After aging, washing, dehydration and drying, nickel-cobalt-manganese hydroxide with an aluminum coating is obtained. The first sintering is then performed to obtain the first modified precursor. The temperature of the first sintering is 400~500℃, and the time of the first sintering is 8~12h; S4. Dissolve the silicon source in an alkaline solution to obtain a silicon source solution; mix the first modified precursor with the silicon source solution, stir evenly at room temperature, and dry to obtain the second modified precursor; S5. The second modified precursor is mixed with a lithium source, subjected to a second sintering, and ground to obtain the LiAlSiO4 coated modified cathode material.

2. The method for preparing a LiAlSiO4-coated modified cathode material according to claim 1, characterized in that, In step S1, the nickel salt includes at least one of nickel sulfate, nickel chloride, and nickel nitrate; And / or, the cobalt salt includes at least one of cobalt sulfate, cobalt chloride, and cobalt nitrate; And / or, the manganese salt includes at least one of manganese sulfate, manganese chloride, and manganese nitrate.

3. The method for preparing a LiAlSiO4-coated modified cathode material according to claim 1, characterized in that, In step S3, the base solution is obtained by mixing water, alkaline solution and ammonia solution; the pH of the base solution is 10-14, and the ammonia concentration of the base solution is 10-15 g / L. During the coprecipitation reaction, the pH is controlled at 10-14, the ammonia concentration at 10-15 g / L, the rotation speed at 300-1100 rpm, and the reaction temperature at 30-65℃.

4. The method for preparing a LiAlSiO4-coated modified cathode material according to claim 1, characterized in that, In step S3, when the aluminum-alkali mixed solution is simultaneously dripped into the reaction vessel, the molar ratio of Al element in the aluminum-alkali mixed solution to nickel, cobalt and manganese metal elements in the metal mixed solution is a:(100-a), 0.5≤a≤3.

5. The method for preparing a LiAlSiO4-coated modified cathode material according to claim 1, characterized in that, In step S3, the chemical formula of the nickel-cobalt-manganese hydroxide with the aluminum coating layer is Ni x Co y Mn z Al (1-x-y-z) (OH)2, where x≥0.85, 0.01<y<0.1, 0.01<z<0.

1.

6. The method for preparing a LiAlSiO4-coated modified cathode material according to claim 1, characterized in that, In step S3, the first target particle size is 9.0~10.0μm, and the second target particle size is 10.0~11.0μm.

7. The method for preparing a LiAlSiO4-coated modified cathode material according to claim 1, characterized in that, In step S4, the silicon source includes anhydrous sodium metasilicate and / or sodium metasilicate hydrate. And / or, the concentration of the silicon source solution is 0.02~0.05mol / L, and the pH of the silicon source solution is 10~11; And / or, the solid-liquid ratio of the first modified precursor to the silicon source solution is 1 g: (15~20) mL.

8. The method for preparing a LiAlSiO4-coated modified cathode material according to claim 1, characterized in that, In step S5, when the second modified precursor is mixed with the lithium source, the molar ratio Li:Me is controlled to be (1.03-1.05):1, where Me represents Ni, Co, Mn and Al; And / or, the lithium source includes lithium hydroxide and / or lithium carbonate; And / or, the second sintering temperature is 800~900℃, the second sintering time is 15~20h, and the sintering atmosphere of the second sintering is pure oxygen.

9. A LiAlSiO4 coated modified cathode material, characterized in that, It is prepared by the method for preparing LiAlSiO4 coated modified cathode material according to any one of claims 1 to 8.

10. A lithium battery, characterized in that, The raw materials used in the preparation include the LiAlSiO4 coated and modified cathode material as described in claim 9.

Citation Information

Patent Citations

  • Lithium silicate-coated Ni-Co lithium aluminate positive electrode material and preparation method thereof

    CN107910539A

  • High-nickel material coated with aluminum and lithium silicate on surface and doped with fluorine on surface layer and preparation method

    CN108807931A